Molecular signature of extracellular matrix pathology in schizophrenia. (13th November 2020) - Pantazopoulos, Harry; Katsel, Pavel; Haroutunian, Vahram; Chelini, Gabriele; Klengel, Torsten; Berretta, Sabina
Abstract: Growing evidence points to a critical involvement of the extracellular matrix (ECM) in the pathophysiology of schizophrenia (SZ). Decreases of perineuronal nets (PNNs) and altered expression of chondroitin sulphate proteoglycans (CSPGs) in glial cells have been identified in several brain regions. GWAS data have identified several SZ vulnerability variants of genes encoding for ECM molecules. Given the potential relevance of ECM functions to the pathophysiology of this disorder, it is necessary to understand the extent of ECM changes across brain regions, their region‐ and sex‐specificity and which ECM components contribute to these changes. We tested the hypothesis that the expression of genes encoding for ECM molecules may be broadly disrupted in SZ across several cortical and subcortical brain regions and include key ECM components as well as factors such as ECM posttranslational modifications and regulator factors. Gene expression profiling of 14 neocortical brain regions, caudate, putamen and hippocampus from control subjects ( n  = 14/region) and subjects with SZ ( n  = 16/region) was conducted using Affymetrix microarray analysis. Analysis across brain regions revealed widespread dysregulation of ECM gene expression in cortical and subcortical brain regions in SZ, impacting several ECM functional key components. SRGN, CD44, ADAMTS1, ADAM10, BCAN, NCAN and SEMA4G showed some of the most robust changes. Region‐, sex‐ and age‐specific gene expression patterns and correlation with cognitive scores were also detected. Taken together, these findings contribute to emerging evidence for large‐scale ECM dysregulation in SZ and point to molecular pathways involved in PNN decreases, glial cell dysfunction and cognitive impairment in SZ. Abstract : Growing evidence points to a critical involvement of the extracellular matrix (ECM) in the pathophysiology of schizophrenia (SZ). We tested the hypothesis that the expression of genes encoding for ECM molecules may be broadly disrupted in SZ across several cortical and subcortical brain regions. Gene expression profiling of 14 neocortical brain regions, caudate, putamen and hippocampus from control subjects and donors with SZ was conducted using Affymetrix microarray analysis. Analysis across brain regions revealed widespread dysregulation of ECM gene expression in cortical and subcortical brain regions in SZ. In (a) proportion of ECM‐related differentially expressed genes (DEG) in SZ by the brain regions. The superior temporal cortex (BA22) showed the highest number of DEGs. In (b) ECM‐related DEGs in SZ compared to UC across all of the analysed regions (blue‐downregulated; red‐upregulated). DEG's t ‐score ( Y axis) values plotted against fold change ( X axis).